Answer:
Step-by-step explanation:
The tough part of this question is figuring out what to do with √(7^2). You could do it by expanding the square. √(7^2) = √49
Now what is the square root of 49? Is it not 7?
√49 = 7
7^6 * 7^1
7 ^(6 + 1)
7 ^ 7
Answer:
49
Step-by-step explanation:
Which points are a distance of 5 units from (2, 3) if ? (7, 3) (–1, –1) (0, 3) (2, 8) (−7, 6)
Answer:
(7, 3), (–1, –1) and (2, 8) are at a distance of units from (2, 3).
Step-by-step explanation:
We know that the formula of distance is given by:
Distance = [tex]\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}[/tex]
So substituting the given points points to check which points are at a distance of 5 units from [tex](2,3)[/tex].
1. (2, 3) and (7, 3):
[tex]\sqrt{(7-2)^2+(3-3)^2} =\sqrt{25} = 5[/tex]
2. (2, 3) and (–1, –1):
[tex]\sqrt{(-1-2)^2+(-1-3)^2} =\sqrt{25} = 5[/tex]
3. (2, 3) and (0, 3):
[tex]\sqrt{(0-2)^2+(3-3)^2} =\sqrt{4} = 2[/tex]
4. (2, 3) and (2, 8):
[tex]\sqrt{(2-2)^2+(8-3)^2} =\sqrt{25} = 5[/tex]
5. (2, 3) and (-7, 6):
[tex]\sqrt{(-7-2)^2+(6-3)^2} =\sqrt{90} =9.5[/tex]
Answer:
Step-by-step explanation:
The correct answer are A B and D
I just took the test
Find the value of x in the picture
Answer: [tex]x=129\°[/tex]
Step-by-step explanation:
By definition, it is important to remember that:
[tex]Angle\ formed\ by\ two\ chords=\frac{1}{2}(Sum\ of\ intercepted\ arcs)[/tex])
You can observe in the figure that "x" is an Angle formed by two chords, therefore, you can find its value applying the formula.
Therefore, the value of "x" is this:
[tex]x=\frac{1}{2}(204\°+54\°)\\\\x=\frac{1}{2}(258\°)\\\\x=129\°[/tex]
I need to find q, r, s, t
The function is g(x)=2x^2-8
Answer:
q=0
r=2
s=3
t=-3
Step-by-step explanation:
q represents the value we should get from evaluating d(-8).
[tex]d(x)=-\sqrt{\frac{1}{2}x+4}[/tex]
To find d(-8) we use this function here labeled d and replace x with -8:
[tex]d(-8)=-\sqrt{\frac{1}{2}(-8)+4}[/tex]
[tex]d(-8)=-\sqrt{-4+4}[/tex]
[tex]d(-8)=-\sqrt{0}[/tex]
[tex]d(-8)=0[/tex]
So q is 0 since d(-8)=0.
r represents the value we should get from evaluating f(0).
[tex]f(x)=\sqrt{\frac{1}{2}x+4}[/tex]
To find f(0) we use this function labeled f and repalce x with 0:
[tex]f(0)=\sqrt{\frac{1}{2}(0)+4}[/tex]
[tex]f(0)=\sqrt{0+4}[/tex]
[tex]f(0)=\sqrt{4}[/tex]
[tex]f(0)=2[/tex]
So r is 2 since f(0)=2.
s represents the value we should get from evaluating f(10).
[tex]f(x)=\sqrt{\frac{1}{2}x+4}[/tex]
To find f(10) we use this function labeled f and replace x with 10:
[tex]f(10)=\sqrt{\frac{1}{2}(10)+4}[/tex]
[tex]f(10)=\sqrt{5+4}[/tex]
[tex]f(10)=\sqrt{9}[/tex]
[tex]f(10)=3[/tex]
So s is 3 since f(10)=3.
t represents the value we should get from evaluating d(10).
[tex]d(x)=-\sqrt{\frac{1}{2}x+4}[/tex]
To find d(10) we use the function labeled d and replace x with 10:
[tex]d(10)=-\sqrt{\frac{1}{2}(10)+4}[/tex]
[tex]d(10)=-\sqrt{5+4}[/tex]
[tex]d(10)=-\sqrt{9}[/tex]
[tex]d(10)=-3[/tex]
So t is -3 since d(10)=-3
q=0
r=2
s=3
t=-3
What is the common difference between successive terms in the sequence?
0.36, 0.26, 0.16, 0.06, –0.04, –0.14, ...
Answer:
-.1
Step-by-step explanation:
The common difference in the arithmetic sequence can be found by doing term minus a previous term.
So 0.26-0.36=-.1
or 0.16-0.26=-.1
or 0.06-0.16=-.1
or -0.04-0.06=-.1
or -0.14-(-0.04)=-.1
you roll a fair 6 sided die what is p (not 5)
Answer:
5/6
Step-by-step explanation:
There are 6 possible rolls
1 2 3 4 5 6
Only one of 6 is a five
A video game requires at least 4 points to advance. Each solved puzzle is worth two points. Each solved riddle is worth 1 point. If x is the number of solved puzzles and y is the number of solved riddles, which graph represents this scenario?
PLZ HELP IM TIMED
Answer:
The graph in the attached figure
Step-by-step explanation:
Let
x -----> the number of solved puzzles
y -----> the number of solved riddles
we know that
[tex]2x+y \geq 4[/tex]
The solution of the inequality is the shaded area above the solid line [tex]2x+y=4[/tex]
The slope of the solid line is negative [tex]m=-2[/tex]
The y-intercept of the solid line is the point (0,4)
The x-intercept of the solid line is the point (2,0)
therefore
The graph in the attached figure
Answer:
The graph that representss this scenario is attached.
Explanation:
You can create the graph by determining the expression that shows the relationship between the variables and then drawing the graph in a coordinate system.
1. Determine the expression that relates the variables.
a) The name of the variables is given:
x: number of solved puzzles
y: number of solved riddles
b) Point rules:
Each solved puzzle is worth two points: 2x
Each solved riddle is worth 1 point: 1y = y
Sum of points: 2x + y
The video game requires at least 4 points to advance: this means that the number of points must grater than or equal to 4 ⇒ 2x + y ≥ 4 .
In conclusion, it has been determined that the expression that rules the system of points is the inequality 2x + y ≥ 4.
2) Building the graph
Solve algebraically for y: y ≥ 4 - 2x
You want to draw the border line of the function, that is y = 4 - 2x
You have a linear function, so you need only two points to draw it. It is generally easier to work with the intercepts.
x-intercept (y = 0) ⇒ 2x + 0 = 4 ⇒ 2x = 4 ⇒ x = 2 ⇒ point (2, 0)
y-intercept (x = 0) ⇒ 2(0) + y = 4 ⇒ y = 4 ⇒ point (0, 4).
In conclusion, you can use the points (2,0) and (0,4) to draw the line that is the border of your graph.
Addtional constrains: x and y cannot be negative, so add the constrains:
x ≥ 0 and y ≥ 0
The set of solutions of y ≥ 4 - 2x is the same line y = 4 - 2x and the region over the line, so you have to shade that portion of the graph, but only in the first quadrant (since x and are greater than or equal to zero).
plz give brainliest
(-b3+ 3b2 + 8) - (? - 5b2 - 9) = 5b3 + 8b2 + 17
? =
DONE
Answer with Step-by-step explanation:
Let ?=x
We have to find the value of x in:
[tex](-b^3+3b^2+8)-(x-5b^2-9)=5b^3+8b^2+17[/tex]
Adding [tex]b^3[/tex] on both sides, we get
[tex]-b^3+3b^2+8-x+5b^2+9+b^3=5b^3+8b^2+17+b^3[/tex]
[tex]3b^2+8-x+5b^2+9=5b^3+8b^2+17+b^3[/tex]
Combining the like terms on both side, we get
[tex]8b^2+17-x=6b^3+8b^2+17[/tex]
Subtracting both sides by 8b², we get
[tex]8b^2-x+17-8b^2=6b^3+8b^2+17-8b^2[/tex]
[tex]-x+17=6b^3+17[/tex]
subtracting both sides by 17, we get
[tex]-x+17-17=6b^3+17-17[/tex]
[tex]-x=6b^3[/tex]
Dividing both sides by -1, we get
[tex]x=-6b^3[/tex]
Hence, ? = [tex]-6b^3[/tex]
Find the selling price of a $50 item after a 50 % markup
Answer:
75 dollars
Step-by-step explanation:
If an item is 50 and you want to markup 50%, you must find 50% of 50 to find how much the item will go up by from 50.
So 50% of 50 means 50% times 50.
50%=.5 or 1/2
So .5(50)=25.
The item is going up by 25 dollars.
So we started at 50 dollars.
So 50+25 is going to be the new amount.
50+25=75 is the new amount.
$75
Step-by-step explanation:In this question, it's asking you to find the selling price of an item after the markup.
We know that:
Item is $50There is a 50% markupWith the information above, we can find the answer.
A markup is pretty much an increase in a price. This means that in this context, the item's price increased by 50%
We're going to need to find how much the selling price is after the markup.
We would multiply 50 by 1.5 to find the selling price.
[tex]50*1.5=75\\\\\text{Or you can do it this way}\\\\50*0.5=25\\\\50+25=75[/tex]
With either method, you're still going to get 75.
This means that the selling price of the item after applying the markup value is $75
I hope this helps you out.Good luck on your academics.Have a fantastic day!What are the solutions of the equation x^2=9
To solve this you must completely isolate x. This means that you have to get rid of the square from the x. To do this take the square root of both sides (square root is the opposite of squaring something and will cancel the square from the x)
√x² = √9
x = 3
and
x = -3
Check:
3² = 9
3*3 = 9
9 = 9
(-3)² = 9
-3 * -3 = 9
9 = 9
Hope this helped!
~Just a girl in love with Shawn Mendes
Which of the following describes a compound event?
A. Tossing a coin and getting heads
B. Drawing the ace of hearts from a deck of cards
C. Rolling 2 on a die
D. Drawing an ace from a deck of cards and getting heads on a coin
toss
HELP PLEASE
Answer:
D. Drawing an ace from a deck of cards and getting heads on a coin
toss
Step-by-step explanation:
Drawing an ace from a deck of cards and getting heads on a coin
toss describes a compound event.
Answer:
D. Drawing an ace from a deck of cards and getting heads on a coin
toss.
Step-by-step explanation:
Compound event means being able to get more than one different outcome in any given time. This means that the result is not always the same. Most of the time, this consists of more than one event, and that the event has nothing to do with each other (independent compound events).
~
An 'A' is considered 4.0, a 'B' is 3.0, a 'C' is 2.0, a 'D' is 1.0, and an 'F' is 0. If you received the following grades in your first semester, what would your grade point average be?
English: 3.0 credits, B.
Biology: 4.0 credits, B.
Communications: 3.0, F.
New student seminar: 1.0, A.
Express your answer rounded to the hundredths place.
Answer:
Your grade point average would be 2.75(B- or C+)
Step-by-step explanation:
[tex]\frac{3+4+3+1}{4} \\\frac{11}{4} \\2.75[/tex]
Final answer:
Explaining the calculation of GPA based on given grades, resulting in an approximate value rounded to the hundredths place.
Explanation:
The grade point average (GPA) for the given grades can be calculated as follows:
English: 3.0 credits, B, which is 3.0 in GPA scale
Biology: 4.0 credits, B, which is 3.0 in GPA scale
Communications: 3.0, F, which is 0.0 in GPA scale
New student seminar: 1.0, A, which is 4.0 in GPA scale
Calculating the GPA:
(3.0 + 3.0 + 0.0 + 4.0) / 11 = 10.0 / 11 = 0.91
Therefore, the grade point average would be approximately 0.91 rounded to the hundredths place.
Simplify the expression.
-(10)^-2
Answer:
-1/100
Step-by-step explanation:
-(10)^-2
Exponents first
We need to make the negative in the exponent positive, which means move it to the denominator
-1
--------
10^2
-1
---------
100
Answer:
-1/100
Step-by-step explanation:
10^(-2) becomes 1/100.
-(10)^(-2) is -1/100.
Evaluate the following vertices for the function f(x)=x+2y
Answer:
You might want to see if I read your ordered pairs right because it was really hard to see for me:
f(2,6)=14
f(-1,3)=5
f(6,4)=14
Step-by-step explanation:
I assume they meant to write f(x,y)=x+2y.
Doing f(2,6) now. This means replace x with 2 and y with 6:
f(2,6)=2+2(6)=2+12=14
f(2,6)=14
Doing f(-1,3) now. This means replace x with -1 and y with 3:
f(-1,3)=-1+2(3)=-1+6=5
f(-1,3)=5
Doing f(6,4) now. This means replace x with 6 and y with 4:
f(6,4)=6+2(4)=6+8=14
f(6,4)=14
Tha values of the function f(2, 6), f(-1, 3) and f(6, 4) are 1, 5 and 14 respectively
Functions and valuesGive the function expressed as:
f(x, y) = x + 2y
If the coordinate point is (2, 6), then;
f(2, 6) = 2 + 2(6)
f(2, 6) = 2 + 12
f(2, 6) = 14
If the coordinate point is (-1, 3), then;
f(-1, 3) = -1 + 2(3)
f(-1, 3) = -1 + 6
f(-1, 3) = 5
If the coordinate point is (6, 4), then;
f(6, 4) = 6 + 2(4)
f(6, 4) = 6 + 8
f(6, 4) = 14
Hence the values of the function f(2, 6), f(-1, 3) and f(6, 4) are 1, 5 and 14 respectively
Learn more on function and values here: https://brainly.com/question/4934333
to the nearest hundreth, what is the circumference of a circle with a radius of 7 units?
Answer:153.94
Step-by-step explanation:circumference is πr^2
π × 49 = 153.93804
Nearest hundredth count two digits after the decimal(to make an hundredth), then round off with the third number
HELP ASAP!!! IM BEING TIMED. Use synthetic division to test one potential root. Enter the numbers that complete the division problem.
Step-by-step explanation:
1 * (-5) = -5 a = -5
6 + (-5) = 1 b = 1
1 * (-5 ) = -5 c = -5
-7 + -5 = -12 d = -12
The divisor of the polynomial in the synthetic long division is linear factor
The correct values are;
a = -5c = -5b = 1d = -12Reason:
[tex]-5 \underline{\left \lfloor{ \begin{matrix}1 & 6 & -7 &-60 \\ &a & c & 60\end{matrix}}} \underset \hspace {} \hspace {0.6 cm} 1 \ \ b \hspace {0.25 cm} d \hspace {0.25 cm} 0[/tex]
The divisor in the division is (x - (-5)) = (x + 5)
By synthetic long division, we have;
Carry down the 1 representing the leading coefficient
[tex]-5 \underline{\left \lfloor{ \begin{matrix}1 & 6 & -7 &-60 \\ & & & \end{matrix}}} \underset \hspace {} \hspace {0.6 cm} 1[/tex]Multiply the 1 brought down by the zero value of x which is -5, and take the result into the second line of the division symbol
-5 × 1 = -5
[tex]-5 \underline{\left \lfloor{ \begin{matrix}1 & 6 & -7 &-60 \\ &-5 & & \end{matrix}}} \underset \hspace {} \hspace {0.6 cm} 1[/tex]Add the coefficient 6 to -5, and bring down the result
[tex]-5 \underline{\left \lfloor{ \begin{matrix}1 & 6 & -7 &-60 \\ &-5 & & \end{matrix}}} \underset \hspace {} \hspace {0.6 cm} 1 \ \ \ 1[/tex]Repeat the above steps again to get;
-5 × 1 = -5
[tex]-5 \underline{\left \lfloor{ \begin{matrix}1 & 6 & -7 &-60 \\ &-5 & -5 & \end{matrix}}} \underset \hspace {} \hspace {0.6 cm} 1 \ \ \ 1 \hspace {0.3 cm} -12[/tex]-5 × (-12) = 60
[tex]-5 \underline{\left \lfloor{ \begin{matrix}1 & 6 & -7 &-60 \\ &-5 & -5 & 60\end{matrix}}} \underset \hspace {} \hspace {0.6 cm} 1 \ \ \ 1 \hspace {0.25 cm} -12 \hspace {0.25 cm} 0[/tex]By comparison to the given synthetic long division, [tex]-5 \underline{\left \lfloor{ \begin{matrix}1 & 6 & -7 &-60 \\ &a & c & 60\end{matrix}}} \underset \hspace {} \hspace {0.6 cm} 1 \ \ b \hspace {0.25 cm} d \hspace {0.25 cm} 0[/tex], we have;
a = -5, c = -5, b = 1, and d = -12
Learn more about synthetic long division here:
https://brainly.com/question/14261063
Bev earns $2 a week for taking out her neighbor’s trash cans. Complete the table of values. Then state the domain and range.
Number of Weeks | Money Earned
1 |
2 |
3 |
4 |
Answer with Step-by-step explanation:
Bev earns $2 a week for taking out her neighbor’s trash cans.
Number of Weeks Money Earned ($)
1 2
2 4
3 6
4 8
As we can see the domain is the number of weeks which is:
{1,2,3,4,...}
and Range is the money earned in dollars which is:
{2,4,6,8,...}
10x^3+40x^2+15x
------------------------------
5x
Answer:
Step-by-step explanation:
[tex]\dfrac{10x^3 + 40x^2 + 15x}{5x}\\ \dfrac{10x^3}{5x} +\dfrac{40x^2}{5x}+\dfrac{15x}{5x}[/tex]
2x^2 + 8x + 3 is your final answer.
Triangles ABD, CBD and ADC are all isosceles. Find the angle x.
AC = AD
Measure of angle 'x' given in the picture will be 36°.
From the picture attached,
In ΔABD,
m∠DAB = x° [Given]
AB ≅ BD [Isosceles triangle]
Therefore, opposite sides of the given triangles will measure the same.
m∠BAD = m∠BDA = x°
m∠BAD + m∠BDA + m∠ABD = 180° [By triangle sum theorem]
x° + x° + m∠ABD = 180°
m∠ABD = 180°- 2x°
m∠DBC + m∠ABD = 180° [Linear pair of angles]
m∠DBC + (180° - 2x) = 180°
m∠DBC = 2x°
In isosceles ΔBCD,
BD ≅ CD
Therefore, m∠DBC = m∠BCD = 2x°
In isosceles ΔACD,
Since, AC ≅ AD,
Therefore, m∠ACD = m∠ADC = 2x°
By applying triangle sum theorem in ΔACD,
m∠ACD + m∠DAC + m∠CDA = 180°
2x° + x° + 2x° = 180°
5x° = 180°
x = 36°
Therefore, measure of 'x' will be 36°.
Learn more,
https://brainly.com/question/1153593
For the parent function y=√x what effect does a value of k = -3 have on the graph?
Horizontal shift of 3 units to the right
Horizontal shift of 3 units to the left
Vertical shift of 3 units up
Vertical shift of 3 units down
Answer:
Vertical shift of 3 units down ⇒ last answer
Step-by-step explanation:
* Lets revise the translation of a function
- If the function f(x) translated horizontally to the right
by h units, then the new function g(x) = f(x - h)
- If the function f(x) translated horizontally to the left
by h units, then the new function g(x) = f(x + h)
- If the function f(x) translated vertically up
by k units, then the new function g(x) = f(x) + k
- If the function f(x) translated vertically down
by k units, then the new function g(x) = f(x) – k
* Lets solve the problem
∵ The parent function y = √x
∵ There is a translation by k = -3
- From the rules above k is for the vertical translation
∵ k = -3
- That means the parent function translated 3 units down
∴ The value of k = -3 makes the graph of the parent function translated
3 units down
- For more understand look to the attached graph
# y = √x ⇒ the red graph
# y = √x - 3 ⇒ the blue graph
Ryan has 57 plastic blocks that are either yellow or green. In 57-X, what does x equal?
Answer:
the amount of green blocks = X then you'll end up with the amount of yellow blocks
Answer:
so x can be either yellow or green
Step-by-step explanation:
Ryan has total 57 blocks (total yellow and green)
if x is either of yellow or green
then 57 -x will be either green or yellow (According to x is green or yellow)
x can be either yellow or green .
Evaluate |c^2 +b^2|, given a=5, b=-3, and c=-2.
2
6
10
13
Answer:
13Step-by-step explanation:
|a| = a for a ≥ 0
|a| = -a for a < 0
============================================
|c² + b²|
Put b = -3 and c = -2 to the expression:
|(-2)² + (-3)²| = |4 + 9| = |13| = 13
simplify each of the following exponential expressions:
a.
[tex] {7}^{2} [/tex]
b.
[tex] {6}^{3} [/tex]
c.
[tex] {12}^{2} [/tex]
d.
[tex] {2}^{4} [/tex]
e.
[tex] {10}^{3} [/tex]
Answer:
the answer is A
Step-by-step explanation:
jewels has 6.75 to ride the ferry around Connecticut m it will cost her 0.45 every time she rides. identify the dependent variable and independent variable in this scenario
the number of rides is the independent variable and the total cost is the dependent variable
the total cost is the independent variable and the number of rides is the dependent variable
the number of rides and the total cost are both independent variables
the number of rides and total cost are both dependent variables
Answer:
Dependent would be the number of times she rides because it would add up to how many times she could ride. 6.75= x(.45)
Step-by-step explanation:
In Jewels' ferry ride scenario, the independent variable is the number of rides taken, and the dependent variable is the total cost incurred based on the rides. This follows the general rule where the dependent variable's outcome is determined by the choice made in the independent variable.
Explanation:In the scenario described, Jewels has a certain amount of money to spend on ferry rides, and each ride costs a fixed amount. Here, the number of ferry rides she can take is the independent variable, as it can be chosen freely by Jewels. The total cost of the ferry rides is the dependent variable, as it depends on the number of rides she takes.
Therefore, the correct answer is that the number of rides is the independent variable and the total cost is the dependent variable.
As for the given reference information, in the vacation resort case, the number of hours the equipment is rented is the independent variable, and the total fee is the dependent variable. This is similar to Jewels' scenario because the basic principle in both instances is about the relationship between a variable you can control (number of rides or hours) and a variable that depends on this control (total cost or total fee).
For example, if Jewels decides to ride the ferry 5 times, the total cost would be 5 rides × $0.45 per ride = $2.25. This demonstrates how the dependent variable (total cost) changes in response to a change in the independent variable (number of rides).
64 -[16 x (-3) – 2 x{17 – 25 }]
Answer:
96
Step-by-step explanation:
64 -[16 x (-3) – 2 x{17 – 25 }] I'm going to take a couple of steps that are very small and they can be combines along with other steps. Combine 16*-3
64 - [-48 - 2*(17 - 25)] Combine what is inside (17 - 25)
64 - [-48 - 2*(-8)] Combine -2*-8
64 - [-48 + 16] Combine what is in the brackets.
64 - [-32] Remove the brackets
64 + 32 Combine
96
The trick in this question is the signs.
The variable z is directly proportional to x. When x is 3, z has the value 48. What is the value of z when x = 7?
Answer:
112
Step-by-step explanation:
Given z is directly proportional to x then the equation relating them is
z = kx ← k is the constant of proportionality
To find k use the condition x = 3 when z = 48
k = [tex]\frac{z}{x}[/tex] = [tex]\frac{48}{3}[/tex] = 16, thus
z = 16x ← equation of proportionality
When x = 7, then
z = 16 × 7 = 112
A side of a square is 8 3/2 inches. Using the area formula A = s2, determine the area of the square.
Answer:
Area=512 square inches
Step-by-step explanation:
According to the given data;
A side of a square = (8)³/² inches.
Area of a square = ?
To find the area of a square we use the formula:
Area = s²
Area=(8)³/²)²
Area = 8³
Area= 8*8*8
Area=512 square inches....
Determine the equivalent system for the given system of equations:
2x + 3y = 7
4x – 2y = 4
A.2x + 3y = 7
8x – 4y = 4
B.2x + 3y = 7
6x + y = 11
C.-2x – 3y = 7
4x - 2y = 4
D.2x + 3y = 7
6x + y = 4
Answer:
[tex]\large\boxed{B.\ \left\{\begin{array}{ccc}2x+3y=7\\6x+y=11\end{array}\right}[/tex]
Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}2x+3y=7&(1)\\4x-2y=4&(2)\end{array}\right\\\\\underline{+\left\{\begin{array}{ccc}2x+3y=7\\4x-2y=4\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad6x+y=11\qquad(3)\\\\\text{Make the system of equation with (1) and (3):}\\\\\left\{\begin{array}{ccc}2x+3y=7\\6x+y=11\end{array}\right[/tex]
The equivalent system of equations for the given system of equations is
option (B)
[tex]2x+3y=7\\6x+y=11[/tex]
This is obtained by adding the given equations.
Equivalent system of equations:Systems of equations that have the same solution are called equivalent systems. Given a system of two equations, we can produce an equivalent system by replacing one equation with the sum of the two equations, or by replacing an equation with a multiple of itself.Calculating the equivalent system for the given system of equations:Given the system of equations as
[tex]2x+3y=7\\4x-2y=4[/tex]
Adding the two equations,
[tex]2x+3y+4x-2y=7+4\\6x+y=11[/tex]
Therefore, the system of equations
[tex]2x+3y=7\\6x+y=11[/tex]
are equivalent to the given set of equations.
Thus, option (B) is correct.
Learn more about the equivalent system of equations here:
https://brainly.com/question/13028509
#SPJ2
2x^2+y^2=8xy find dy/dx
Answer:
2(x-2y)/(4x-y) = dy/dx
Step-by-step explanation:
2x^2+y^2=8xy
Take the derivative of each term, remembering that we take the 8xy as derivative by parts)
2 * 2x dx + *2y dy = 8 ( x dy + dx *y)
4x dx +2y dy = 8x dy + 8y dx
Subtract 2y dy from each side
4x dx +2y dy -4y dy = 8x dy - 2y dy + 8y dx
4x dx = 8x dy - 2y dy + 8y dx
Subtract 8y dx from each side
4x dx -8y dx = 8x dy - 2y dy + 8y dx-8y dx
4x dx -8y dx = 8x dy - 2y dy
(4x-8y) dx = (8x-2y) dy
Factor out a 4 from the left side and a 2 from the right side
4(x-2y) dx = 2( 4x-y) dy
Cancel a 2
2(x-2y) dx = ( 4x-y) dy
Divide each side by (4x-y)
2(x-2y)/(4x-y) dx = ( 4x-y)/(4x-y) dy
2(x-2y)/(4x-y) dx = dy
Divide by dx
2(x-2y)/(4x-y) dx/dx = dy/dx
2(x-2y)/(4x-y) = dy/dx
what is the slope of the line shown below? (9, 1) (-3, -7)
Answer:
2/3
Step-by-step explanation:
To find the slope based off of two points, use the following formula:
[tex]\frac{y2-y1}{x2-x1}[/tex]
Plug in your values and simplify.
[tex]\frac{-7-1}{-3-9} \\\\\frac{-8}{-12}[/tex]
[tex]\frac{8}{12}[/tex]
[tex]\frac{2}{3}[/tex]
Answer:
2/3
Step-by-step explanation:
I like the line up and subtract strategy. At the end you just put 2nd number over 1st.
This is the slope formula; just a different way to think about the formula.
(9,1)
-(-3,-7)
=======
12, 8
So the slope is 8/12=2/3.
Which of the following does not have triangular faces?
A. Dodecahedron
B. Icosahedron
C. Octahedron
D. Tetrahedron
Answer:
Step-by-step explanation:
Answer "A"
Dodecahedron
Dodecahedron does not have triangular faces.
What is Dodecahedron?The dodecahedron is also known as pentagonal dodecahedron which is composed of 12 regular pentagonal faces, 30 edges, and 20 vertices.
A regular icosahedron is a 3D polyhedron having 20 triangular faces, 30 edges, and 12 vertices.
A regular octahedron has 8 triangular faces, 6 vertices, and 12 edges.
A tetrahedron has 4 triangular faces, 4 vertices, and 6 edges.
All of these 3 have triangular faces.
But Dodecahedron has 12 faces which are pentagonal in shape.
Therefore Dodecahedron does not have triangular faces.
Learn more about Dodecahedron
here: https://brainly.com/question/2273338
#SPJ2